(untitled) (Journal of Kidney Cancer, 2019)
Cytoreductive nephrectomy has been an integral part of management in metastatic renal cell carcinoma for patients with good performance status, based on the benefit shown by prospective trials in the interferon era and retrospective trials in the targeted therapies era. Clinical Trial to Assess the Importance of Nephrectomy (CARMENA), the first prospective phase III trial comparing a targeted agent alone (sunitinib) versus nephrectomy plus sunitinib, has been recently published, showing non-inferiority for the nephrectomy-sparing arm. In this article, we discuss the impact of nephrectomy including its immune-mediated effects, surgical morbidity and mortality, and the clinical data supporting the indications of nephrectomy in order to analyze the CARMENA trial in context, with the aim to identify optimal strategies for different patient populations in the metastatic setting.